The CRISPR-Cas System Is Involved in OmpR Genetic Regulation for Outer Membrane Protein Synthesis in Salmonella Typhi - Medina-Aparicio, Liliana; Rodriguez-Gutierrez, Sarahí; Rebollar-Flores, Javier E.; Martínez-Batallar, Ángel G.; Mendoza-Mejía, Blanca D.; Aguirre-Partida, Eira D.; Vázquez, Alejandra; Encarnación, Sergio; Calva, Edmundo; Hernández-Lucas, Ismael (Frontiers in Microbiology, 2021)
The CRISPR-Cas cluster is found in many prokaryotic genomes including those of the Enterobacteriaceae family. Salmonella enterica serovar Typhi (S. Typhi) harbors a Type I-E CRISPR-Cas locus composed of cas3, cse1, cse2, cas7, cas5, cas6e, cas1, cas2 and a CRISPR1 array. In this work, it was determined that in the absence of cas5 or cas2, the amount of the OmpC porin decreased substantially, whereas in individual cse2, cas6e, cas1 or cas3 null mutants, the OmpF porin was not observed in an electrophoretic profile of outer membrane proteins. Furthermore, the LysR-type transcriptional regulator LeuO was unable to positively regulate the expression of the quiescent OmpS2 porin, in individual S. Typhi cse2, cas5, cas6e, cas1, cas2 and cas3 mutants. Remarkably, the expression of the master porin regulator OmpR was dependent on the Cse2, Cas5, Cas6e, Cas1, Cas2 and Cas3 proteins. Therefore, the data suggest that the CRISPR-Cas system acts hierarchically on OmpR to control the synthesis of outer membrane proteins in S. Typhi.